Solar Energy 2003
DOI: 10.1115/isec2003-44037
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Production by Solar Thermochemical Water-Splitting/Methane-Reforming Process

Abstract: Two different routes of solar thermochemical hydrogen production are reviewed. One is two-step water splitting cycle by using a metal-oxide redox pair. The first step is based on the thermal reduction of metal oxide, which is a highly endothermic process driven by concentrated solar thermal energy. The second step involves water decomposition with the thermally-reduced metal oxide. The first thermal reduction process requires very-high temperatures, which may be realized in sun-belt regions. Another hydrogen p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…Since the Ru with Alumina support had the most stable activity, it also had the highest chemical efficiency of approximately 50% and the highest methane conversion of 73% [49]. Figure 10 shows that the metal absorber achieves better conversion than the ceramic absorber under the same conditions [48,49,50]. The higher conductivity of the metallic absorber improves the temperature uniformity and hence the chemical efficiency; however, other factors could effect the latter including catalyst dispersion and radiative heat transfer so it is unclear which factors lead to better performance.…”
Section: ]mentioning
confidence: 79%
See 1 more Smart Citation
“…Since the Ru with Alumina support had the most stable activity, it also had the highest chemical efficiency of approximately 50% and the highest methane conversion of 73% [49]. Figure 10 shows that the metal absorber achieves better conversion than the ceramic absorber under the same conditions [48,49,50]. The higher conductivity of the metallic absorber improves the temperature uniformity and hence the chemical efficiency; however, other factors could effect the latter including catalyst dispersion and radiative heat transfer so it is unclear which factors lead to better performance.…”
Section: ]mentioning
confidence: 79%
“…Moving on to systems that utilize a catalyst, a lab-scale study of dry reforming was done using a porous absorber reformer with different absorbers and catalysts integrated with a solar-simulated Xe-arc lamp light [48,49,50].…”
Section: ]mentioning
confidence: 99%
“…The coated ZrO 2 particles were tested and the cyclic reaction could be repeated at temperatures of 1673 K for thermal reduction and 1273 K for water splitting. ZrO 2 alleviated the sintering of the solid reactant ferrite, and the phase transformation between Fe 3 O 4 and FeO occurred on the crystals of ZrO 2 [61]. Pure Fe 3 O 4 as well as different ferrites of the form M x Fe 3− x O 4 were coated on ZrO 2 particles (particle size of about 1 µm) and tested, (M = Mn, Co, Mg Ni) [49,62,63].…”
Section: Metal Oxide-based Redox Materialsmentioning
confidence: 99%
“…This is due to melting and sintering of iron oxide particles at high temperature. The present authors first demonstrated repeatable two-step water-splitting in 2003, using highly active ''ZrO 2 -supported'' ferrite particles [11][12][13]. The supporting ZrO 2 alleviated agglomeration or sintering of the solid ferrite reactant, and as a result the cyclic reaction could be repeated with relatively good activity in the temperature range of 1000-1400 1C.…”
Section: Introductionmentioning
confidence: 96%